Transcriptional Control of Cardiac Fuel Metabolism and Mitochondrial Function - Leone, T.C. (2011)
As a persistent pump, the mammalian heart demands a high-capacity mitochondrial system. Significant progress has been made in delineating the gene regulatory networks that control mitochondrial biogenesis and function in striated muscle. The PPARγ coactivator-1 (PGC-1) coactivators serve as inducible boosters of downstream transcription factors that control the expression of genes involved in mitochondrial energy transduction, ATP synthesis, and biogenesis. PGC-1 gain-of-function and loss-of-function studies targeting two PGC-1 family members, PGC-1α and PGC-1β, have provided solid evidence that these factors are both necessary and sufficient for perinatal mitochondrial biogenesis and maintenance of high-capacity mitochondrial function in postnatal heart. In humans, during the development of heart failure owing to hypertension or obesity-related diabetes, the activity of the PGC-1 coactivators, and several downstream target transcription factors, is altered. Gene targeting studies in mice have demonstrated that loss of PGC-1α and PGC-1β in heart leads to heart failure. Interestingly, the pattern of dysregulation within the PGC-1 transcriptional regulatory circuit distinguishes the heart disease caused by hypertension from that caused by diabetes. This transcriptional regulatory cascade and downstream metabolic pathways should be considered as targets for novel etiology-specific therapeutics aimed at the early stages of heart failure.